Development of Polyherbal Nutraceutical Formulation for Cardioprotective and Hypolipidemic Activity - Jadhav, Dr. Vijay. B.; Kale, Snehal. S.; Aglawe, Dr. Sachin. B.; Jain, Dr. Nitin. P.; Jain, Dr. Usha. N.; Aghade, Mr. Karveer. B. (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Cardiovascular diseases (CVDs) remain a leading cause of global morbidity and mortality, closely associated with hyperlipidemia, oxidative stress, and altered lipid metabolism. Objective: This study aimed to develop and evaluate a polyherbal nutraceutical formulation possessing cardioprotective and hypolipidemic properties. Methods: Selected medicinal plants with established antioxidant and cardioprotective potential were collected, authenticated, processed, and subjected to standard aqueous extraction procedures. Preliminary phytochemical screening was conducted to identify bioactive constituents. The prepared polyherbal formulation was evaluated for its organoleptic characteristics, physicochemical parameters, stability, and clinical efficacy via serum lipid profile analysis. Serum lipid parameters—including Total Cholesterol (TC), Triglycerides (TG), High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), and Very Low-Density Lipoprotein (VLDL)—were analyzed in six volunteers before and after a 90-day administration period. Results: Preliminary phytochemical screening revealed the presence of flavonoids, tannins, glycosides, phenolic compounds, terpenoids, carbohydrates, and proteins. Treatment with the formulation yielded a significant reduction in TC, TG, LDL, VLDL, and both the LDL/HDL and TC/HDL risk ratios, alongside an improvement in HDL cholesterol levels. The formulation demonstrated acceptable physicochemical properties and satisfactory stability at both room and refrigerated temperatures over 30 days. Conclusion: The observed cardioprotective and hypolipidemic activity may be attributed to the synergistic antioxidant effects of the phytoconstituents. These findings suggest that the developed polyherbal nutraceutical formulation represents a promising, natural therapeutic approach for managing hyperlipidemia and mitigating associated cardiovascular risks.
Keywords: Cardiovascular diseases; Polyherbal nutraceutical formulation; Cardioprotective activity; Hyperlipidemia; Antioxidant activity; Phytochemical screening; Lipid profile; Herbal medicine; Nutraceuticals.